IDENTIFIKASI KESULITAN GURU DALAM PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) KURIKULUM 2013 DI SEKOLAH DASAR GUGUS 1 KEDIRI - Nunung Adha; I Nyoman Karma; Husniati Husniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
This study aims to describe the difficulties of teachers in the preparation of the 2013 curriculum lesson plan (RPP) in Primary School Cluster 1 Kediri, for the Academic Year of 2020/2021. The approach used is a descriptive qualitative approach. Data collection techniques were carried out through interviews, questionnaires, and documentation. Data analysis Model Milles And Huberman were used for data analysis. The result showed that the difficulties experienced by teachers in preparing the 2013 curriculum lesson plans are; 1) difficulties of teachers in developing learning indicators, 2) difficulties of teachers in formulating learning objectives, 3) difficulties of teachers in determining learning models and methods, 4) difficulties of teachers in preparing learning steps, 5) difficulties of teachers in making and developing authentic assessments. This difficulty is caused by several factors, namely; 1) the teacher’s understanding in preparing of the 2013 curriculum RPP is still lacking, 2) lack of training in preparing the 2013 curriculum RPP, 3) not enough time. It can be concluded that teachers at SD Gugus 1 Kediri experienced difficulties in compiling the RPP component of the 2013 curriculum due to several factors. The contributing factors that had the most impact were the teacher’s lack of understanding in the preparation of the 2013 curriculum lesson plans and time insufficiency.